Avaliação automatizada de uma habilidade motora fundamental com o kinect - Sulino, Rafael Macedo [UNESP] (2014)
The assessment of the human body displacement is essential for both, the academic scientific research and the professional practice, especially with regard to the assessment of fundamental movement patterns (FMP) throughout childhood in order to identify possible delays and provide adequate motor intervention. Technologies available recently in the entertainment market, as the Kinect sensor, have great potential for application in several areas, especially with regard the capture and movement analysis, enabling the acquisition of data quickly and efficiently without the use of markers, and at low cost compared to high precision systems available in the Laboratories. In this study we propose a system based on Kinect for automated assessment of the FMP standing long jump. The study was conducted in two stages, including the construction, testing and implementation of the system. The first stage, related to the construction of the system, consisted of the development of algorithms necessary for the acquisition, storage, processing and analysis of data, and the second stage consisted of three experimental studies. In the first study we evaluated the Kinect for static data acquisition, in comparison with the Optotrak, a high precision optical system, with the aim of assessing the accuracy of the device on variation in the capture of three-dimensional coordinates and measure of angles agreement with a high precision laboratory system. The results indicated minimal variation in data acquisition related to fixed points for 50 seconds, and high correlation measures when compared to the Optotrak. In the second study we evaluate the Kinect for dynamic data acquisition, comparing it again with Optotrak in five different joint displacements, and three different speeds. The results indicated that the difference between the measurements obtained from the Kinect compared with the measurements obtained from the Optotrak are within a confidence interval...